Above and belowground traits impacting transpiration decline during soil drying in 48 maize (Zea mays) genotypes. (8th December 2022) - Koehler, Tina; Schaum, Carolin; Tung, Shu-Yin; Steiner, Franziska; Tyborski, Nicolas; Wild, Andreas J; Akale, Asegidew; Pausch, Johanna; Lueders, Tillmann; Wolfrum, Sebastian; Mueller, Carsten W; Vidal, Alix; et al.
Abstract: Background and Aims: Stomatal regulation allows plants to promptly respond to water stress. However, our understanding of the impact of above and belowground hydraulic traits on stomatal regulation remains incomplete. The objective of this study was to investigate how key plant hydraulic traits impact transpiration of maize during soil drying. We hypothesize that the stomatal response to soil drying is related to a loss in soil hydraulic conductivity at the root–soil interface, which in turn depends on plant hydraulic traits. Methods: We investigate the response of 48 contrasting maize ( Zea mays ) genotypes to soil drying, utilizing a novel phenotyping facility. In this context, we measure the relationship between leaf water potential, soil water potential, soil water content and transpiration, as well as root, rhizosphere and aboveground plant traits. Key Results: Genotypes differed in their responsiveness to soil drying. The critical soil water potential at which plants started decreasing transpiration was related to a combination of above and belowground traits: genotypes with a higher maximum transpiration and plant hydraulic conductance as well as a smaller root and rhizosphere system closed stomata at less negative soil water potentials. Conclusions: Our results demonstrate the importance of belowground hydraulics for stomatal regulation and hence drought responsiveness during soil drying. Furthermore, this finding supports the hypothesis that stomata start to close when soil hydraulic conductivity drops at the root–soil interface.